Lubrication and tribological properties of palm oil mixed with organo zinc compound - Md Alias, Muhammad Aizat (2021)
Friction can be defined as the resistance to motion of one object moving relative to each other. At certain application, frictions are required to be used such as for a brake application. Unnecessary friction creates wear, hence reducing the lifespan of equipment and machinery. One of the solution by using a lubricant to reduce friction and wear to a minimum level. Conventional lubricant which is made of petroleum based is not biodegradable, harmful to the environment and the source not renewable. Hence, the purpose of this study was to investigate the lubrication and tribological properties enhancement by using palm oil as parent base oil mixed with organo zinc compound as additive. Besides that, the predominant wear possess by the worn surface of the ball bearing was identified. The oil samples were prepared by mixing organo zinc compound additive; Zinc Dioctyldithiophosphate (ZnDoDP) or Zinc Diamyldithiocarbamate (ZDDC) between 0 wt. % to 3.0 wt. % concentrations interval with commercialized palm oil and then were homogenized using ultrasonic homogenizer (0 wt. %, 1 wt. %, 1.5 wt. %,2.0 wt.%,2.5 wt. %, 3.0 wt. %) Afterward, the oil sample was tested for their oil properties in accordance to engineering standard in terms of elemental analysis test, viscosity index test, small scale flashpoint test and potentiometric titration acid number test (automatic). Then, the tribological test was performed using a four-ball tribometer in accordance to ASTM D4172. The worn surfaces of the balls were observed using a Scanning Electron Microscope and Energy-dispersive X-ray spectroscopy. The results show that commercialized palm oil with 2.0 wt. % of ZnDoDP had an excellent characteristic in terms of its lubrication and tribological properties than commercialized palm oil with 0 wt. % (ZnDoDP and ZDDC) and commercialized palm oil with the addition of 2.0 wt. % of ZDDC. As a conclusion, palm oil mixed with organo zinc compound as additive enhanced the lubrication properties at 2.0 wt.%, decrease about 20.5% (ZDDC) and 7.9% (ZnDoDP) in their viscosity index and decrease the value of flashpoint about 11.6% (ZDDC) and 15.1% (ZnDoDP) from commercialized palm oil with 0 wt. % additive . Meanwhile, as for their acid number, there are an increased value of about 61% (ZDDC) and 97% (ZnDoDP) from conventional transmission oil. In terms of tribological properties, it shows that at 2.0 wt. %, about 22 % (ZDDC) and 60% (ZnDoDP) value decrease of wear scar diameter from pure palm oil. Meanwhile, the value of the coefficient of friction also decreases if compared to commercialized palm oil with 0 wt. % additive about 36.8% (ZDDC) and 43% (ZnDoDP) resulted in producing an alternative lubricant which can be applied in industry in as substitution to conventional mineral based oil as lubricant.